2015
DOI: 10.1039/c5ta00727e
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanosheets, carbon nanotubes, graphite, and activated carbon as anode materials for sodium-ion batteries

Abstract: The graphene nanosheet electrode with excellent high-rate performance and satisfactory cyclability is an ideal anode for sodium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(103 citation statements)
references
References 33 publications
3
98
1
1
Order By: Relevance
“…It is known that anode materials widely used in current LIBs usually cannot deliver good performance as well in SIBs, such as graphite [4,5]. Many efforts are devoted to carbonaceous materials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that anode materials widely used in current LIBs usually cannot deliver good performance as well in SIBs, such as graphite [4,5]. Many efforts are devoted to carbonaceous materials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…After a couple of cycles, the CVs were stable and rectangular shaped in the higher potential region. This indicates a capacitive storage behaviour attributed to electro-adsorption/desorption of sodium-ions in RGOs [17,48]. Also, the overlapping of the CV curves in the subsequent cycles is indicative of good battery stability and reversible sodium-ion interaction.…”
Section: Electrochemical Performance Vs Na/na +mentioning
confidence: 84%
“…The use of such graphene nanosheets as electrode materials for NIBs, although not as prevalent in the literature as for LIBs, have started to emerge recently [14][15][16][17][18][19]. It has been demonstrated that thermally reduced graphene oxide (RGO) with a d-spacing of 3.7 Å displayed a specific capacity of 174 mA h g -1 at a current density of 40 mA g -1 [15].…”
Section: Introductionmentioning
confidence: 99%
“…[102] Nitrogen doping of MWCNT decreased the first cycle Coulombic efficiency due to irreversible binding of lithium to pyridinic nitrogen atoms but improved the electrochemical storage kinetics. [105] MWCNTs exhibit poorer cycling stability, along with less than half the sodium insertion capacity of SWCNTs, due to the less ordered internal environment, resulting in 30 mAh g −1 after 100 cycles. [104] In comparison, CNTs have shown less relative success for sodium ion storage.…”
Section: Carbon Nanotubesmentioning
confidence: 99%